Crispin at the edge of the world - Avi (New York Hyperion Books for Children, 2006)
Branded as traitors by the king's authorities, Crispin and his guardian, Bear, flee to coastal towns in fourteenth-century England, where they perform a musical juggling act and bond as a family after befriending a disfigured girl.
Sequel to: Crispin, the cross of lead.
A Junior Library Guild selection.
88212
Keywords: Middle Ages -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Great Britain -- History -- Richard II, 1377-1399 -- Juvenile fiction